Identification of Novel Adjuvants for Ebola Virus-Like Particle Vaccine - Huapeng Feng; Sumiho Nakatsu; Tiago Jose da Silva Lopes; Masaki Imai; Seiya Yamayoshi; Makoto Yamashita; Tokiko Watanabe; Yoshihiro Kawaoka (Vaccines, 2020)
Ebola virus disease is a severe disease, often fatal, with a mortality rate of up to 90%. Presently, effective treatment and safe prevention options for Ebola virus disease are not available. Therefore, there is an urgent need to develop control measures to prevent or limit future Ebola virus outbreaks. Ebola virus protein-based virus-like particle (VLP) and inactivated whole virion vaccines have demonstrated efficacy in animal models, and the addition of appropriate adjuvants may provide additional benefits to these vaccines, including enhanced immune responses. In this study, we screened 24 compounds from injectable excipients approved for human use in Japan and identified six compounds that significantly enhanced the humoral response to Ebola VLP vaccine in a murine model. Our novel adjuvant candidates for Ebola VLP vaccine have already been demonstrated to be safe when administered intramuscularly or subcutaneously, and therefore, they are closer to clinical trials than adjuvants whose safety profiles are unknown.